Docencia e investigación en la Educación Superior: revisión crítica con Gimeno Sacristán - María José Chisvert Tarazona (Universitat Politècnica de València, 2012)
José Gimeno Sacristán, pedagogo erudito, pensador crítico, es un adelantado a su tiempo, prueba de ello es que ha participado en los procesos de resignificación de la realidad educativa en el Estado español. Recientemente investido como Doctor Honoris Causa en las Universidades de San Luis (Argentina) y Málaga (España), ha sido profesor en la Universidad Complutense de Madrid, en la de Salamanca y, desde 1981, en la de Valencia. Esta entrevista refleja su mirada crítica y reconstruye su biografía profesional. Las dimensiones tratadas nos permiten conocer sus inicios como docente, sus reflexiones sobre los referentes y principios que han participado en la definición de su pensamiento, sus análisis sobre las políticas y prácticas universitarias, sobre la investigación. También realiza una revisión histórica de la evolución del currículum en los estudios de educación en las Universidades españolas. En definitiva se trasladan sus ideas, sus creencias relativas al espacio universitario contextualizadas en su historia de vida.   ABSTRACTS Teaching and Research in Higher Education: Critical Review by Gimeno Sacristán José Gimeno Sacristán, knowledgeable educationalist, critical thinker, is advanced to his time. Proof of it is his contribution to the processes of renewal and resignification of educational understanding and policy in Spain. He has recently been awarded the title of Doctor Honoris Causa in the Universities of San Luis (Argentina) and Málaga (Spain). He was formerly lecturer in the Universidad Complutense in Madrid, Professor in the Universidad de Salamanca and, since 1981, he has been Professor in the Universitat de València. In this interview he shares his critical views and looks back at his own professional biography. Several dimensions appear along the interview that allow us to know his studies and early professional years, his reflections about those who have been key academic references as well as the principles upon which he has developed his professional practice, his thinking and his analysis of university policies and practices in both teaching and research domains. He also invites us to review the development of curriculum studies in education degrees in contemporary Spanish Universities. This interview portrays his ideas and beliefs about higher education upon the background of his own life history.